Is rituximab an effective treatment of refractory calcinosis?. (31st May 2016) - Dubos, Maria; Ly, Kim; Martel, Clothilde; Fauchais, Anne Laure
Abstract : Calcinosis, the deposition of calcified material in soft tissues, is frequently seen in systemic sclerosis and dermatomyositis. Treatment options are limited, with disappointing results. Some recent case reports suggest that rituximab may be an attractive therapeutic option. In case 1, a 54-year-old woman who presented with rheumatoid arthritis in association with scleromyositis was treated with rituximab for rheumatoid arthritis. Despite this, she developed multiple progressive calcinosis, necessitating extracorporeal shock wave lithotripsy to limit calcinosis extension and pain. In case 2, a 38-year-old man, previously treated for an anti-Pm/Scl-positive polymyositis/scleroderma overlap syndrome, presented with multiple tumoural periarticular calcinosis, which progressed despite bisphosphonates, sodium thiosulfate and thalidomide. We decided to start rituximab. Progression of calcinosis was still evident 6 and 12 months after anti-CD20 treatment. Many treatments have been tried to treat calcinosis without demonstrated effectiveness. Presently, rituximab cannot be recommended for this indication in the absence of successful controlled trials.